Let's get ready an experiential follow-through journey toolkit and multi-sensory safe space for children ages 4-7 to circumvent separation anxiety during school opening - Solas, Diego Stefano C.
Refusal behavior are often exhibited by preschool pupils during school opening. It is expected for a child to show signs of discomfort when being critically cut off from the source of protection since the children are only beginning to grasp the sense of the world that is why it is very important to take consider their behavior. Though it is considered normal as part of the child's nature and development, it has the potential to grapple onto a much greater distress if it has persisted to a certain extent. Most of the main caregivers pictured this phenomenon as if the child can simply disconnect their emotional bonds, which is one of the major source of distress that makes the first day of school traumatic.